2019
DOI: 10.1016/j.tpb.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

A generalization of the informational view of non-random mating: Models with variable population frequencies

Abstract: Mate choice may generate non-random mating patterns. It has been recently shown that the mating distribution caused by mate choice can be expressed as a gain in information with respect to random mating. In that model, the population phenotypic frequencies were assumed as constant during the breeding season. In the present work such restriction was relaxed to consider different encounter-mating processes in which the population frequencies of available individuals change over mating rounds. As with the constan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…However, the above assumption is likely to be violated in the case of monogamous species with low population size, or even in large population sizes with local competition for mates (if the number of individuals in the patches is low) and/or space-temporal constraints. In such cases, the mating process resembles a sampling without replacement and the population phenotype frequencies may be altered during the reproductive season so that the sexual selection and assortative mating patterns would be more difficult to detect (Carvajal-Rodríguez 2019). In fact, the simulations (see Appendix C) showed that the performance of the multi-model inference is affected by the sampling and the mating system (polygamous or monogamous) but it is still quite robust for detecting non-random mating in the parameter values except in the worst scenario of monogamous species with small population sizes.…”
Section: Simulationsmentioning
confidence: 99%
“…However, the above assumption is likely to be violated in the case of monogamous species with low population size, or even in large population sizes with local competition for mates (if the number of individuals in the patches is low) and/or space-temporal constraints. In such cases, the mating process resembles a sampling without replacement and the population phenotype frequencies may be altered during the reproductive season so that the sexual selection and assortative mating patterns would be more difficult to detect (Carvajal-Rodríguez 2019). In fact, the simulations (see Appendix C) showed that the performance of the multi-model inference is affected by the sampling and the mating system (polygamous or monogamous) but it is still quite robust for detecting non-random mating in the parameter values except in the worst scenario of monogamous species with small population sizes.…”
Section: Simulationsmentioning
confidence: 99%
“…See Refs. [2,3] for extensive explanation about individual or mass-encounters.Out_MateSim_massEM_8_ac2-3_driftnonU_sample50_N10000_MPF0.1:Mass-encounter model 8 with female competition ( a = 2) plus choice compound-parameter model ( c = 3). Sample size is 50 matings from a population of size N = 10 000.…”
Section: Data Descriptionmentioning
confidence: 99%
“…To compare different types’ fitness fairly, we compute the relative fitness, w i , as the ratio of their absolute fitness to the mean population fitness. Thus, for a given type i with frequency p i , the new frequency p ’ i after a selection episode will be given by (Bürger 2000; Hansen 2018) Recently, a simple theoretical framework, similar to the model presented in (1), has been developed to describe the influence of mating competition and mate choice on the emergence of sexual selection and assortative mating patterns (Carvajal-Rodríguez 2018b, 2019, 2020). This theoretical framework has enabled the development of new statistical tests for detecting sexual selection and assortative mating.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous studies (Carvajal-Rodríguez, 2019, 2018a), it was demonstrated that non-random mating can be effectively quantified using the Jeffreys (Kullback-Leibler symmetrized) divergence. This measure captures the information acquired when mating is influenced by mutual mating propensities, rather than occurring randomly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation